Alignment of a wavefront-guided scleral lens correction in the presence of a lens capsulotomy. Issue 6 (December 2020) - Nguyen, Lan Chi; Hastings, Gareth D.; Kauffman, Matthew J.; Applegate, Raymond A.; Marsack, Jason D.
Highlights: Wavefront-guided scleral lenses improve vision and decrease higher order aberrations in ectasia and post-surgical corneas. Alignment of wavefront-guided scleral lens corrections to the underlying optics of an eye over the effective pupil is crucial. The pupil, as defined by the iris, is not always the limiting aperture of the eye. Abstract: Purpose: To demonstrate the necessity of aligning a wavefront-guided scleral lens (WGSL) optical correction to the eye's effective pupil, with misalignments leading to reduced performance. Case report: A 34 year old subject with a history of failed LASIK in the left eye, leading to penetrating keratoplasty, extracapsular extraction of the crystalline lens and neodymium:yttrium-aluminum-garnet (Nd:YAG) laser posterior capsulotomy, enrolled in a study examining WGSL performance. Habitual logMAR acuity OS (aided with a scleral lens) was +0.04. Residual higher order root mean square (HORMS) wavefront error (WFE) was 0.28 μm (Φ =4.75 mm, mean age-matched norm =0.17 μm), and objective over-refraction was –0.30 –0.54 × 008. When a WGSL (targeting aberrations up to the 5 th radial order) was manufactured with the wavefront-guided optics aligned to the center of the dilated pupil, logMAR acuity worsened to +0.15, residual HORMS WFE worsened to 0.44 μm (Φ =4.75 mm), and objective over-refraction increased to +1.19 –0.30 × 122. Slit lamp imagery revealed that the effective pupil was no longer defined by the iris of the eye, but rather the capsular opening created by the capsulotomy. When the WGSL was redesigned to align the wavefront-guided optics to the center of the capsular opening, logMAR acuity improved to –0.14, residual HORMS WFE reduced to 0.17 μm (Φ =4.75 mm) and objective over-refraction reduced to +0.20 –0.15 × 111. Conclusion: WGSLs are an emerging option for patients with highly aberrated, ectatic and post-surgical corneas whose visual symptoms cannot be alleviated with conventional corrections. However, alignment of the optics of the WGSL to the underlying optics of the eye over the effective pupil is critical in achieving good optical and visual performance.